The Prospect of Controlling Parasitic Deseases with Biological Agents - Mangaraja P Tampubolon (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
Generally, parasitic diseases in animals may be caused by protozoa, ectoparasites and helminthes. The diseases appearing in the hosts may range from delicate to fatal disturbances depending on the parasite types, pathogeny, location, and various factors. The diseases may be spread directly or though vectors. In'the area ofanimal health, including veterinary world, tropical diseases spread by vectors are the main cause for morbidity and mortality in developing countries. Unwise use of pesticides has caused many negative impacts both in the form of resistance to the disease vectors and to the environment. The utilization of biological agents or natural enemies is generally known as biological control for pest organism . Biological control has been carried out in the area of agricultural and plantation, mainly using predators for pest insects. The use of parasitic and pathogenic agents in biological control appeared much later. Several natural enemies have reached the operational utilization or extensive trial stage. Among them are Bacillus thuringiensis and B. spahericus. Those showing prospect are fungi, such as Lagenidium giganteum with industrial scale prospect. Invertebrate predator Toxorhynchites sp. has a good natural control potency as shown by the experiment result in the field. The presence of effective and save biological control will extensively support the disease control. In this paper, the use of nematofagus fungus as an alternative for nematode control in the ruminant digestive system is used as an example. Key words: Parasitic disease, biological control, animal